Звезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активнаЗвезда не активна
 
\begin{equation} 1){(4e^{x})}'=4e^{x}; \end{equation} \begin{equation} 2){(e^{5x})}'=5e^{5x}; \end{equation} \begin{equation} 3){y}'=3x^{2}*e^{x}+x^{3}*e^{x}=x^{2}e^{x}(3+x); \end{equation} \begin{equation} 4){y}'=e^{x}\sin x + e^{x}\cos x=e^{x}(\sin x + \cos x); \end{equation} \begin{equation} 5){y}'=\frac{e^{x}(x-2)-e^{x}}{(x-2)^{2}}=\frac{e^{x}(x-2-1)}{(x-2)^{2}}= \end{equation} \begin{equation} =\frac{e^{x}(x-3)}{(x-2)^{2}}; \end{equation} \begin{equation} 6){y}'={(e^{x})}'+{(e^{-x})}'=e^{x}-e^{-x}; \end{equation} \begin{equation} 7){y}'={(5^{x})}'=5^{x}\ln 5; \end{equation} \begin{equation} 8){y}'={(2^{x^{2}})}'=2^{x^{2}}\ln 2*2x=2^{x^{2}}*2x\ln 2; \end{equation} \begin{equation} 9){y}'={(7^{2x-3})}'= 7^{2x-3}* \end{equation} \begin{equation} *\ln 7*2=2 \ln 7*7^{2x-3}; \end{equation} \begin{equation} 10){y}'={(x*3^{x})}'=3^{x}+x*3^{x} \ln 3= \end{equation} \begin{equation} =3^{x}(1+ \ln 3 *x); \end{equation}